Strukturnaya klassifikatsiya i zapis' podgotovitel'nykh dvizhenii tyazheloatleta v predvaritel'nykh startakh v rybke i tolchke - Volkov, NP. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of this study was to solve the problem of revealation the specific classificational signsto create the structure classification of the athlete's preparatory movements. The matrix had been elaborated for discription of all the variables of preparatory movements. The specific number of every unit is represented by three figures from 111 to 138, in which the first figure means the matrix's number, the second - the starting position of the athlete, the third - his final position. This method makes more easy coach's and athlete's choice of the units they need to use in various situations of instructing, learning and training.